Effect of zeolite and boric acid on epoxy-based composites; Polymers for Advanced Technologies; Vol. 27, iss. 8 - Putkhenpurakalchira M. V. Maniyan Visakkh; Nazarenko O. B. Olga Bronislavovna; Amelkovich Yu. A. Yuliya Alexandrovna; Melnikova T. V. Tatjyana Vyacheslavovna (2016, 2016)
Title screen